Personal Branding Selebgram Qamara Ashara melalui Media Sosial - Fiet Febriyanti; Edison Bonar Tua Hutapea (Syntax Corporation Indonesia, 2024)
The presence of social media Instagram and TikTok which are currently very popular with internet users, and also their presence which has many advanced features have been chosen as personal branding media, one of which is a Celebgram named Qamara Ashara. Qamara uses Instagram (@qamara.asr) and TikTok (@qamaraasr) accounts as a medium to build communication, build branding about herself, and promote herself as a Celebgram so that she can be known as a brand that has its own meaning and significance to the general public. This study was conducted using the constructivism paradigm. The method used is qualitative descriptive, and the data collection techniques used are through observation, documentation, and in-depth analysis of social media content. The descriptive study that the researcher chose aims to systematically describe how Qamara Ashara as a Celebgram builds personal branding through her Instagram and TikTok social media accounts. The description begins with how Qamara Ashara wants to display her personal branding by utilizing the features on Instagram and TikTok. The results of this study reveal that Qamara Ashara chooses personal branding through her personal Instagram and TikTok accounts by utilizing the features contained therein. As a Selebgram, Qamara Ashara has fulfilled all the main concepts of the eight laws of personal branding; the law of specialization, the law of leadership, the law of personality, the law of distinctiveness, the law of visibility, the law of unity, the law of persistence, and the law of goodwill. Qamara Ashara's personal branding also fulfills the characteristics of a strong personal brand because it fulfills distinctive, relevant and consistent elements.